Influences of water deficiency on the productivity of young plants at different sites - Sárdi, Katalin (Acta Agraria Debreceniensis, 2018)
Water deficiency has become one of the most limiting factors of crop production in Hungary as the tendency in annual amounts of precipitation shows a decreasing tendency; therefore, it has become similar to those of Southern Europe. The most significant decrease in precipitation occurs typically during spring, approximately 20% of the data expressed in the averages of the last century. Studying the relationship between water deficiency as a stress factor and nutrient supply is important in order to improve the production efficiency of crops. Nowadays, this problem receives outstanding attention presented in numerous papers both in Hungary and globally, however, there are several questions yet to be answered. Our pot experiments were carried out under controlled greenhouse conditions in order to establish new data on these relationships. Experimental soils were typical for Western Transdanubia, taken from long-term field experiments representing four different site characteristics of the region. It was concluded from the results that drought periods during the early growth stages (i.e. 4–5 weeks after emergence) of plants may result in significant decreases in both dry matter production, nutrient concentrations, nutrient uptake and shoot:root ratios. Better nutrient supply, especially potassium, plays a significant role in reducing the negative effects of water deficiency.